Loan Default among Cooperative Women Entrepreneur in Ifo Local Government Area of Ogun State, Nigeria - Oluwasanya, Oluwakayode Peter; Ogunmuyiwa, M. S.; Aladegoroye, O. R.; Akerele, Ezekiel O.; Olabisi, Monsurat I. (NIU Journal of Social Sciences, 2020)
Cooperatives have been identified as powerful vehicles of economic, social and political empowerment for women; especially those taking part in entrepreneurial activities. Many rural credit schemes and especially cooperatives, have sustained heavy losses because of loan default. This has been in the public domain but little has been done because cooperative are not regarded as financial institutions. This study investigated the causes of loan default among cooperative women entrepreneurs in Ifo Local Government Area of Ogun State, Nigeria. 120 women entrepreneur were selected using multi-stage sampling techniques, structured questionnaire were used to obtain data from the women entrepreneur. Data were analysed using descriptive statistics and Logit regression model. Results obtained on the socio-economic characteristics of the respondentsâ€™ show that majority of the respondents were between the aged group 22 - 30 (35.0%) with an average age of 41 years per entrepreneur and mostly (50.8%) practiced Islam. 47.5% were married and 82.5% had one form of formal education or the other. Factors that determine loan default among the women entrepreneur revealed credit amount received, monthly income, interest on loan and marital status emerged as reliable predictors of women loan default in the study area. It can be concluded that  business failure, late disbursement of fund, inadequate loan sizes, unforeseen contingencies (such as illness and death of a family member) and high interest rate were major factors that cause loan default while, obtaining flexible payment terms, timely disbursement of the loan, adequate loan sizes, reasonable interest rate, training before and after disbursement, monitoring of client business activities and available information on client integrity were found to be best measures to control loan default. Therefore, proper training should be done to enhance the borrowersâ€™ products marketability, financial management and accounting proficiency in order to boast their business performances for reasonable profit to accrue for settlement of the loan they borrowed and Credit supervisor should check with credit officers daily to ensure that policies are followed and the supervisor must respond quickly to solve credit officersâ€™ problems. Keywords: Causes, Loan default, Cooperative, Women entrepreneurs,